AI-integrated interactive learning: Advancing engagement, creativity, and critical thinking in Indonesian language learning - Dwi Agus Setiawan; Novika Adi Wibowo (UIN Raden Mas Said Surakarta, 2025)
The present study investigates the implementation of interactive learning strategies within an Indonesian Language Development course, aiming to enhance the overall learning process. Specifically, it seeks to identify and analyze effective interactive strategies that incorporate artificial intelligence (AI) platforms in Indonesian language instruction at the higher education level. Employing a qualitative case study design, data were meticulously collected from twelve (12) undergraduate students enrolled in the Elementary School Teacher Education Program through in-depth interviews and classroom observations. The study was conducted in a course delivered using interactive learning strategies supported by various AI and digital platforms (e.g., ChatGPT, DeepSeek, YouTube, interactive digital presentations, and video conferencing tools). Data validity was rigorously ensured through prolonged engagement, member checking, collegial discussions, and the triangulation of sources, techniques, and theories. The analytical process involved data collection, condensation, display, and conclusion drawing. The findings reveal that the integration of AI platforms as learning media significantly: (1) boosts active participation, (2) facilitates more adaptive and personalized learning, (3) empowers students in designing creative content, (4) refines writing and language analysis skills, and (5) fosters reflective motivation and critical thinking in language learning. Integrating AI within interactive learning strategies presents an innovative approach to elevating the quality of Indonesian language teaching and learning in higher education. Future studies are encouraged to explore the continued development of AI technologies to maximize their impact in educational settings.